Taking Stock of Corpus-Based Instruction in Teaching English as an International Language. (December 2018) - Huang, Li-Shih
Corpora are essential tools in the teaching of English as an international language (EIL). With the advent of high-powered computers, online corpora have been developed with the potential to transform how EIL is taught both inside and outside the classroom, since anyone with a mobile device and internet access can now take advantage of numerous corpora databases. But applying computer corpora to language pedagogy also requires teacher mediation; moreover, the issues involving the lack of corpus integration in either the EIL language classroom or teacher training programmes are both challenging and complex. Nonetheless, there is hope that empowering teachers with the necessary tools, skills, and knowledge in using online corpora will lead to the day when corpora resources and their use are no longer the exclusive preserve of researchers and reference material developers.